A Formal Syntactic Anaylsis of Agentivity in Motion Predicates in Ghanaian Student Pidgin (GSP) - Osei-Tutu, Kwaku O. A. (2021)
The paper explores the syntactic structure of Agentive motion predicates in Ghanaian Student Pidgin (GSP), an English-lexified expanded pidgin spoken by (mostly male) students (and young adults) in Ghanaian secondary and tertiary educational institutions. I argue that GSP uses Serial Verb Constructions (SVCs) to encode Agentive motion predicates and propose syntactic analyses to account for the difference in interpretation between Initial Contact Agentives and Continuous Contact Agentives – despite the apparent similarity in their surface structures. The paper argues that though (in accordance with previous studies on agentivity Kratzer, 1996; Pylkkänen, 2008; Harley, 2013) GSP introduces the agent with an agentive vP in both Initial and Continuous Contact agentives, the difference in interpretation between the two results from an embedded make-clause in the underlying structure of Initial Contact agentives which is not present in Continuous Contact agentives.